Răspuns :
(a-b)²=2²⇔a²+b²-2ab=4⇔a²+b²=4+2·4⇔a²+b²=12
a²+b²=(a+b)²-2ab⇔12=(a+b)²-8⇔20=(a+b)²⇒a+b=-√20 sau a+b=√20
a²+b²=(a+b)²-2ab⇔12=(a+b)²-8⇔20=(a+b)²⇒a+b=-√20 sau a+b=√20
Știind ca a-b=2 si a*b=4 ,Calculați a+b
Ridicam diferenta la patrat⇒(a-b)²=2²⇒(a²-2ab+b²)=4 dar ab=4
a²+b²-2×4=4
a²+b²=4+8
a²+b²=12
(a+b)²=a²+2ab+b²⇒a²+b²=(a+b)²-2ab
12=(a+b)²-2×8
20=(a+b)²
⇒a+b=√20
Ridicam diferenta la patrat⇒(a-b)²=2²⇒(a²-2ab+b²)=4 dar ab=4
a²+b²-2×4=4
a²+b²=4+8
a²+b²=12
(a+b)²=a²+2ab+b²⇒a²+b²=(a+b)²-2ab
12=(a+b)²-2×8
20=(a+b)²
⇒a+b=√20